Evaluation of photo-fenton degradation of reactive black 5 using response surface method - Aris, Azmi; Sharratt, Paul N. (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2007)
Photo-Fenton degradation of a reactive dyestuff, Reactive Black 5, was investigated in this study. The effects of UV light on Fenton Reagent process and the influence of reagents dosage, UV light intensity and initial dissolved oxygen concentration on photo-Fenton were explored. The experiments were conducted in a 3-L batch-mode reactor and were designed using Response Surface Method. The performance of the systems was assessed based on TOC removal. UV light was found to increase the efficiency of Fenton Reagent process by about 100%, reduce the reaction time by half and lessen the iron requirement by about 85%. Within the range used in the experiments, UV light intensity, and iron and hydrogen peroxide dosages were found to have significant positive influence on the efficiency of the photo-Fenton process. Iron dosage was significant in the early stage, peroxide dosage was significant at the later stage while UV light intensity was significant throughout the reaction period. The initial dissolved oxygen concentration was not a significant factor for photo-Fenton. Depending on the conditions of the reaction, TOC removal of 41.3% to 88.2% was obtained by photo-Fenton oxidation after 30 minutes.